The Prevalence of Ureaplasma Urealyticum and Mycoplasma Genitalium in Patients with Prostate Cancer in Shohada Hospital in Tehran, Iran - Eslami, Gita; Goudarzi, Hossein; Baseri, Neda; Ghalavand, Zohreh; Taherpour, Arezou; Zhaam, Haniye; Samadi, Roghayeh; Azargashb, Eznolah (Novelty in Biomedicine, 2015)
Background: Prostate cancer (PCa) is an important health problem in the aging male population in the world. It is the third most common cancer in the world. Despite of its importance, relatively little is known about its etiology. Sexually transmitted infections (STI) and urogenital pathogens such as Mycoplasma and Ureaplasma, have been proposed as a risk factor for prostate cancer development. This study aimed at detecting the prevalence of Ureaplasma urealyticum (U. urealyticum) and Mycoplasma genitalium (M. genitalium) in PCa and the controls group with benign prostate hyperplasia (BPH) in Shohada hospital. Materials and Methods: A total of 124 paraffin-embedded prostate tissues (62 PCa patients and 62 controls with BPH) were included in this study. The subjects’specimens were investigated by the polymerase chain reaction method for the presence of U. urealyticum and M. genitalium DNA. Results: U. urealyticum was detected by standard PCR in 1.61% of the 62 PCa patients and there was no DNA U. urealyticum in the 62 controls with BPH. No M. genitalium was detected by standard PCR in the prostates of 124 paraffin-embedded prostate tissues. Conclusion: According to our results, there is no association between M. genitalium and U.urealyticum with PCa. We recommend further studies using a large sample to determine role of Ureaplasma and Mycoplasma in PCa because understanding the role of infectious agents on PCa might be useful for developing new therapeutic approaches and prevention of PCa.